Association Between the Triglyceride–Glucose Index and the Incidence of Diabetes in People With Different Phenotypes of Obesity: A Retrospective Study - Zou, Su; Yang, Chenxi; Shen, Rui; Wei, Xiang; Gong, Junwen; Pan, Yali; Lv, Yang; Xu, Yingjia (Frontiers in Endocrinology, 2021)
Abstract Aim: We aimed to examine the relationship between the Triglyceride–glucose (TyG) index and the incidence of type 2 diabetes in people with different phenotypes of obesity. Methods: From May 1st, 1994 to Dec 31st, 2016, 20,944 participants were enrolled in the medical examination program at Murakami Memorial Hospital to determine the relationship between the TyG index and the incidence of type 2 diabetes in people with different phenotypes of obesity after 6.04 years of follow-up. Results: Besides triglycerides, HbA1c%, and FPG, the incidence of type 2 diabetes was found to be significantly associated with the TyG index (p<0.001), age(p<0.001), body weight (p=0.016), BMI (p=0.003), current smoker (p<0.001) and fatty liver (p<0.001). In participants with visceral fat obesity and/or ectopic fat obesity and normal BMI, the TyG index was significantly associated with the incidence of type 2 diabetes. In patients with BMI≥25mg/m2, although there was a trend of the relationship between the TyG index and the incidence of type 2 diabetes, the relationship was no longer positive. Conclusion In participants with obesity involving visceral fat obesity and/or fatty liver and normal BMI which is not a measure of body fat distribution, there was a significant association between the TyG index and incidence of T2DM.